Tetralithiated tetraazaperopyrene as a key intermediate for the synthesis of functionalized derivatives - Hahn, Lena; Wadepohl, Hubert; Gade, Lutz H. (Organic letters, 2015)
A new synthetic approach to core-functionalized tetraazaperopyrenes (TAPP) is reported. In-situ reaction of 4-fold lithiated TAPP with electrophiles results in the formation of various unprecedented TAPP derivatives, which are highly emissive fluorophores, show promising photophysical and electrochemical properties and act as valuable starting materials. Thus, lithiation of the TAPP core opens up a facile way for developing new organic materials.
Gesehen am 16.03.2021